al-TaÊ¿rÄ«b fÄ« al-Muá¹£á¹alaá¸¥Ät al-Iliktruniyyah wa al-á¹¢iá¸¥á¸¥iyyah bi MauqiÊ¿ mawdoo3.com al-Ê¿Arabiy - Habri, Habri; Roziki, Khafid; Al Anshory, Abdul Muntaqim (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
The development of modern science and technology today makes Arabic have to adapt to new terms that appear. Arabic absorbs foreign words and phrases and becomes part of Arabic through several processes, including the ta'rib process. This study aims to determine the words or terms that indicate the form of ta'rib in electronics and health fields on the mawdoo3.com website and the methods used in the ta'rib process. This research is a qualitative descriptive study with a literature study approach. Data collection techniques used are reading, note-taking, and documentation techniques. The steps in analyzing the data are collecting data from the website, choosing the word or term ta'rib, describing the data and classifying it in tabular form, and drawing conclusions. The study's results revealed that on the mawdoo3.com website, 61 data were showing the words and terms of ta'rib. The method used in the ta'rib process is the translation method with 41 data, iqtibas lafdzi form with 10 data, isytiqaq method with 9 data, and naht method with 1 data.ÙƒØ§Ù† ØªØ·ÙˆØ± Ø§Ù„Ø¹Ù„ÙˆÙ… ÙˆØ§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ§ Ø§Ù„ØØ¯ÙŠØ«Ø© Ø§Ù„ÙŠÙˆÙ… ÙŠØ¬Ø¹Ù„ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ø¶Ø·Ø±Ø© Ù„Ù„ØªÙƒÙŠÙ Ù…Ø¹ Ø§Ù„Ù…ØµØ·Ù„ØØ§Øª Ø§Ù„Ø¬Ø¯ÙŠØ¯Ø©. ØªÙ…ØªØµ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„ÙƒÙ„Ù…Ø§Øª ÙˆØ§Ù„Ù…ØµØ·Ù„ØØ§Øª Ø§Ù„Ø£Ø¬Ù†Ø¨ÙŠØ© ÙˆØªØµØ¨Ø Ù„ØºØ© Ø¹Ø±Ø¨ÙŠØ© Ù…Ù† Ø®Ù„Ø§Ù„ Ø¹Ø¯Ø© Ø¹Ù…Ù„ÙŠØ§Øª ØŒ Ø¨Ù…Ø§ ÙÙŠ Ø°Ù„Ùƒ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ø±ÙŠØ¨. ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ ØªØÙ„ÙŠÙ„ Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø£Ùˆ Ø§Ù„Ù…ØµØ·Ù„ØØ§Øª Ø§Ù„ØªÙŠ ØªØ¯Ù„ Ø¹Ù„Ù‰ Ø´ÙƒÙ„ Ø§Ù„ØªØ¹Ø±ÙŠØ¨ ÙÙŠ Ø§Ù„Ù…Ø¬Ø§Ù„Ø§Øª Ø§Ù„Ø¥Ù„ÙƒØªØ±ÙˆÙ†ÙŠØ© ÙˆØ§Ù„ØµØÙŠØ© Ø¹Ù„Ù‰ Ù…ÙˆÙ‚Ø¹ mawdoo3.com Â Ø§Ù„Ø¹Ø±Ø¨ÙŠØŒ ÙˆØ§Ù„Ø·Ø±Ù‚ Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ø±ÙŠØ¨. Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¨ØØ« ÙˆØµÙÙŠ Ù†ÙˆØ¹ÙŠ Ù…Ø¹ Ø¯Ø±Ø§Ø³Ø© Ù…ÙƒØªØ¨ÙŠØ©. ØªÙ‚Ù†ÙŠØ§Øª Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© Ù‡ÙŠ ØªÙ‚Ù†ÙŠØ§Øª Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙˆØ§Ù„ØªØ¯ÙˆÙŠÙ† ÙˆØ§Ù„ØªÙˆØ«ÙŠÙ‚. ØªØªÙ…Ø«Ù„ Ø®Ø·ÙˆØ§Øª ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙÙŠ Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù† Ø§Ù„Ù…ÙˆÙ‚Ø¹ ÙˆØ§Ø®ØªÙŠØ§Ø± ÙƒÙ„Ù…Ø§Øª Ø£ÙˆÙ…ØµØ·Ù„ØØ§Øª Ø§Ù„ØªØ¹Ø±ÙŠØ¨ ÙˆÙˆØµÙ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙˆØªØµÙ†ÙŠÙÙ‡Ø§ ÙÙŠ Ø´ÙƒÙ„ Ø¬Ø¯ÙˆÙ„ ÙˆØ§Ø³ØªØ®Ù„Ø§Øµ Ø§Ù„Ù†ØªØ§Ø¦Ø¬. ÙˆÙƒØ´ÙØª Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¹Ù„Ù‰ Ù…ÙˆÙ‚Ø¹ mawdoo3.com Ø£Ù† Ù‡Ù†Ø§Ùƒ 61 Ø¨ÙŠØ§Ù†Ø§Øª ØªÙˆØ¶Ø ÙƒÙ„Ù…Ø§Øª ÙˆÙ…ØµØ·Ù„ØØ§Øª Ø§Ù„ØªØ¹Ø±ÙŠØ¨. Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ø±ÙŠØ¨ Ù‡ÙŠ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ±Ø¬Ù…Ø© Ù…Ø¹ 41 Ø¨ÙŠØ§Ù†Ø§ØªØŒ ÙˆØ·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¥Ù‚ØªØ¨Ø§Ø³ Ø§Ù„Ù„ÙØ¸ÙŠ ÙÙŠ 10 Ø¨ÙŠØ§Ù†Ø§ØªØŒ ÙˆØ·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¥Ø´ØªÙ‚Ø§Ù‚ ÙÙŠ 9 Ø¨ÙŠØ§Ù†Ø§ØªØŒ ÙˆØ·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù†ØØª ÙÙŠ Ø¨ÙŠØ§Ù†Ø§Øª ÙˆØ§ØØ¯Ø©.